Story With Wayang For Children's Therapy Of Speech Delay - Diana Earlyana Lesmana; Nanik Rahayu; Nor Annisa; Emma Rahmani; Septiyani Endang Yunitasari (Edumaspul: Jurnal Pendidikan, 2022)
This study discusses the stimulation of speech delay in Widya Kusuma Sari Kindergarten, Denpasar Bali with the storytelling method. This research uses a qualitative method of case study of a student named Aly who experienced speech delay. Data collection is carried out through observation, interview, and documentation methods. The results showed that storry telling therapy has improved vocabulary treasury, children are able to speak, and communicate simply with their peers, teachers, and parents at home.